Non-Equilibrium Plasma Jet at Atmospheric Pressure Powered by Tesla Coil (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The aim of this work presents the characterization of a plasma jet powered by Tesla coil. Tesla coil can be used for generation cold plasma from Dielectric Barrier Discharge (DBD). Tesla coil has been designed and constructed at Egyptian Atomic Energy Authority for multipurpose. The electrical characteristic of non-equilibrium plasma jet using rare gases (argon and helium) at atmospheric pressure has been studied. An atmospheric-pressure cold plasma jet generated by Tesla coil in a single-electrode configuration is characterized based on optical and electrical measurements.
Keywords: Cold plasma; Plasma jet; DBD; Non-equilibrium plasma; Tesla coil